Happiness Expressions Through WhatsApp Stickers: Semiotic Analysis - ‎Chairunnisa, Chairunnisa; Gultom, Mita Setriana; Octavia, Ocha; Ginting, Teza Aditra (Universitas Muhammadiyah Mataram, 2025)
The rise of WhatsApp stickers has transformed digital communication, enabling richer emotional expression beyond text and emojis. This study investigates how happiness is represented in WhatsApp stickers by applying Ferdinand de Saussure’s semiotic theory, which views meaning as the interaction between the signifier (form) and the signified (concept). Using a descriptive qualitative method, data were collected through observation of WhatsApp chats and short surveys among 5 English Literature students at Universitas Sumatera Utara. Stickers that visually represent happiness were identified and analyzed based on their visual features and users’ interpretations. Results show that happiness is symbolized through big smiles, curved or slit eyes, lively gestures, bright colors, and decorative icons such as hearts, stars, and sparkles. These visual signifiers consistently represent signified meanings of joy, excitement, or satisfaction. The study concludes that WhatsApp stickers serve not just as visual decoration but as meaningful semiotic tools that enhance emotional connection and social bonding in online interaction. This contributes to both theoretical understanding in semiotics and practical insights into digital emotion communication.